AGILE IT SERVICE MANAGEMENT DESIGN OF FINTECHCO DIGITALIZATION BASED ON COBIT 2019 DEVOPS FOCUS AREA - Achmad Fadhli Satriadi; Mulyana, Rahmat; Fauzi, Rokhman (Jurnal Teknik Informatika (Jutif), 2023)
The Indonesian Financial Technology (Fintech) industry plays a pivotal role in driving digital technology advancements and propelling the nation's growth. The rapid development of Fintech presents a unique challenge for established financial companies, necessitating effective government regulation through a Sandbox approach. FintechCo, operating under the watchful eye of State-Owned Enterprises and the Financial Service Authority, must strike a delicate balance between their agile services and security risks. Hence, FintechCo necessitates an examination of optimal agile services through the utilization of five stages derived from the Design Science Research approach. This need arises to adhere to the Good Corporate Governance standards established by State-Owned Enterprises (SOE) and the Financial Services Authority (FSA). The cutting-edge COBIT 2019 DevOps Focus Area framework is employed for analysis. The research identifies three highest priority Governance and Management Objectives (GMOs): Managed Security Services (DSS05), Managed Problem (DSS03), and Managed Solution Identification and Build (BAI03). These GMOs are thoroughly evaluated, and comprehensive recommendations are provided based on their seven key components. There is an estimated 17% increase in the average capability score, from 2.82 to 3.30, across all three GMOs. The contribution of this study is twofold: to serve as a valuable knowledge resource for agile IT services in digitalization within organizations and to offer practical implications for FintechCo to enhance their digitalization. Furthermore, this research sets a precedent for the Fintech industry, signifying a benchmark for excellence and innovation.